Cellular loci involved in the development of brain arteriovenous malformations - Shabani, Zahra; Schuerger, Joana; Su, Hua (Frontiers in Human Neuroscience, 2022)
Brain arteriovenous malformations (bAVMs) are abnormal vessels that are prone to rupture, causing life-threatening intracranial bleeding. The mechanism of bAVM formation is poorly understood. Nevertheless, animal studies revealed that gene mutation in endothelial cells (ECs) and angiogenic stimulation are necessary for bAVM initiation. Evidence collected through analyzing bAVM specimens of human and mouse models indicate that cells other than ECs also are involved in bAVM pathogenesis. Both human and mouse bAVMs vessels showed lower mural cell-coverage, suggesting a role of pericytes and vascular smooth muscle cells (vSMCs) in bAVM pathogenesis. Perivascular astrocytes also are important in maintaining cerebral vascular function and take part in bAVM development. Furthermore, higher inflammatory cytokines in bAVM tissue and blood demonstrate the contribution of inflammatory cells in bAVM progression, and rupture. The goal of this paper is to provide our current understanding of the roles of different cellular loci in bAVM pathogenesis.